CONGENITAL HEART DEFECT IN A PREGNANT WOMAN (CLINICAL CASE) - Елена Валентиновна Гришкевич; Алена Васильевна Иванникова; Елена Николаевна Орлова; Елена Владимировна Рудаева; Светлана Ивановна Елгина; Кира Борисовна Мозес; Елена Германовна Рудаева (Мать и дитя в Кузбассе)
Currently, there is an increase in patients with congenital heart defects. The number of women with cardiovascular pathology planning and carrying a pregnancy does not decrease. Doctors observing such patients must be highly qualified experts in the diagnosis and management of women with various specific congenital heart defects.